IADC/SPE Drilling Conference 2000
DOI: 10.2118/59143-ms
|View full text |Cite
|
Sign up to set email alerts
|

Improved Hole Cleaning and Reduced Rotary Torque by New External Profile on Drilling Equipment

Abstract: This paper will describe the successful application and effects of completely new Hydro mechanical Cleaning and Hydrodynamic Bearing profiles machined externally on drilling equipment to improve hole cleaning and reduce rotary friction. Qualification programmes, including initial proving trials on a test rig, computational fluid dynamics and cuttings transportation flow loop tests, will supplement details from successful field operational use of this equipment. Introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…For instance, the use of downhole mechanical hole cleaning device is a relatively recent drilling innovation. Limited studies (Boulet et al 2000;Sapru 2001;Qureshi 2004;Sagheer 2009) have been carried out to evaluate the performance of these devices. Results of these studies showed that the bed height close to the tools is reduced significantly while the bed remains very thick far from the tool zone.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the use of downhole mechanical hole cleaning device is a relatively recent drilling innovation. Limited studies (Boulet et al 2000;Sapru 2001;Qureshi 2004;Sagheer 2009) have been carried out to evaluate the performance of these devices. Results of these studies showed that the bed height close to the tools is reduced significantly while the bed remains very thick far from the tool zone.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the possible explanations for this is that the turbulence created at the tool gradually diminishes due to viscous dissipation as the fluid flows away from the tool, resulting in redeposition of the cuttings particles on the low-side of the wellbore. Boulet et al (2000) suggested that placement of these tools should be as near as possible to the bottom hole assembly where optimized mechanical behavior of the drillstring and hole cleaning are of the utmost importance. Sapru (2001) conducted bed erosion studies to evaluate the performance of the first generation Hydroclean tools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tests have proven that changing the external profiles of drilling equipments helped to reduce friction and to improve hole cleaning [11]. Tests have proven that changing the external profiles of drilling equipments helped to reduce friction and to improve hole cleaning [11].…”
Section: Technology Used On Extended Reach Drillingmentioning
confidence: 99%
“…The use of a CFD model is proven to be a successful tool in many areas of fluid flow 15,16,17,18 . More applications of CFD exist in the design and manufacture of drill bits and the related bit hydraulics 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%